Electrochemical, Spectroelectrochemical, and Electrochromic Properties of Lanthanide Bis-Phthalocyanines - Orman, Efe Baturhan; Koca, Atif; Ozkaya, Ali Riza; Gurol, Ilke; Durmuş, Mahmut; Ahsen, Vefa (Electrochemical Soc Inc, 2014)
Voltammetric, in-situ spectroelectrochemical, and in-situ electrocolorimetric characterization of octa-2,2,3,3-tetrafluoropropoxy-substituted lanthanide (III) bis-phthalocyanines [samarium(III) (SmPc2), europium (III) (EuPc2), gadolinium (III) (GdPc2), dysprosium( III) (DyPc2) and lutetium(III) (LuPc2)] were performed in solution and in the solid states as Langmuir-Blodgett (LB) films. The type of the central metal of the complexes slightly altered the potentials of the electron transfer reactions. Redox peaks shifted toward the negative potentials as a function of the decreasing metal ion size. All complexes gave three reduction and one oxidation reactions with in the whole potential window of the electrolyte system. Due to the p-p interaction of phthalocyanine rings around the lanthanide metal ions the complexes were easily reduced at even positive potentials. Assignments of the redox processes, spectra and color of the electrogenerated species of the complexes were determined with in-situ spectroelectrochemical, and in-situ electrocolorimetric measurements. Various colors recorded during the electron transfer reactions well reflected electrochromic characters of the complexes. For practical usage, LB thin films of the complexes were easily coated on the ITO electrodes and investigated as electrochromic materials. All complexes displayed three distinctive color alternatives as green, orange, and red for their different redox states. Electrochromic measurements indicated that the nature of the metal ions in the phthalocyanine cavity alters the basic electrochromic parameters of the complexes. LB films of DyPc2 and LuPc2 were especially found as ideal neutral and anodic coloring electrochromic materials with their short response times, and high optical and coulombic stabilities. (C) 2014 The Electrochemical Society. All rights reserved.
Keywords: Langmuir-Blodgett-Films; Lutetium(Iii) Phthalocyanine; Complexes; Spectroscopy; Sensor